Participation in 12-Step Programs and Drug Use Among Older Adults With Cannabis Use Disorder: Six-Month Outcomes. (January 2021) - Woodhead, Erin L.; Brief, Deborah; Below, Maureen; Timko, Christine
This study examined associations among cannabis use disorder (CUD), 12-step program participation, and cannabis and other drug use at baseline and 3- and 6-month follow-ups. Participants were age 50 or older in a study of veterans receiving medical management of alcohol and/or opioid withdrawal ( N = 171). Generalized estimating equations examined the extent to which time point, 12-step program participation, and CUD were associated with change in number of cannabis and non-cannabis drug use days. Also examined was whether having CUD was associated with 12-step program participation. From baseline through the 6-month follow-up, 12-step program participation increased, non-cannabis drug use decreased, and cannabis use remained stable. Twelve-step program participation at baseline was associated with better outcomes at follow-ups. Participants with CUD reported less 12-step program participation and more cannabis use days at follow-ups. Older adults with CUD may need other types of psychosocial treatments due to low participation in 12-step programs.